Cu carbonyls enhance the performance of Ru-based SILP water–gas shift catalysts: a combined in situ DRIFTS and DFT study. Issue 1 (12th December 2019) - Blaumeiser, Dominik; Stepić, Robert; Wolf, Patrick; Wick, Christian R.; Haumann, Marco; Wasserscheid, Peter; Smith, David M.; Smith, Ana-Sunčana; Bauer, Tanja; Libuda, Jörg
Abstract : In situ DRIFT spectroscopy and DFT identify Cu carbonyl shuttles that enhance the performance of Ru-based SILP water–gas shift catalysts. Abstract : Ru-based supported ionic liquid phase (SILP) catalysts efficiently promote the water–gas shift reaction (WGSR). The addition of CuCl further improves the performance. This is attributed to the formation of labile Cu carbonyl species, which act as CO shuttles in the ionic liquid (IL) phase. We apply in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) to monitor the formation of these Cu carbonyls in an imidazolium-based SILP system. To aid the identification of the relevant Cu carbonyls, we perform density functional theory (DFT) calculations. In the present study, we investigate [Ru(CO)3 Cl2 ]2 /CuCl/[C4 C1 C1 Im]Cl/Al2 O3 and CuCl/[C4 C1 C1 Im]Cl/Al2 O3 with various CuCl : IL ratios. The relevant Cu carbonyls are identified as neutral CuCl monomers and dimers, as well as monoanionic monomers and dimers. Moreover, we demonstrate that the ratio of the individual Cu carbonyl species depends on the CuCl : IL ratio.